Numerical analysis of the support system in the transition zone of the Esfahan subway project - Bagherzadeh, A.; Ferdosi, Behnam; Nakhaei, J.; Nasri, M. (2014)
This paper presents the design and 3D numerical modeling of the temporary support system for the twin tunnels in the transition zone of the Esfahan subway project. Ground movements caused by tunneling beneath urban areas can have a significant impact on adjacent structures and therefore require consideration when choosing the excavation method and the type of support system. Due to the old buildings in the historical city of Esfahan, this research requires parametric studies for the use of simulation techniques. This paper focuses on 3D stability analysis and design of the support system required to control the critical strain and ground movement due to excavation of the transition area of the twin tunnels in the Esfahan subway project. A numerical model is developed to estimate the excavation effects on the critical strain and ground settlement and also the effect of reinforcement measures. In the 3D numerical model, a constitutive law characterized by the time-dependent stiffness and strength of the shotcrete is employed. Results show that the suggested support is sufficient to control the settlement and critical strain due to tunneling. Comparison between the 2D model prediction and the results of corresponding 3D model indicates that the conformity between 2D and 3D analysis results decreases in the transition region. One of the most useful methods to determine the induced seismic loads, the use of time-history dynamic analysis is usually done for major projects. In this paper, for the twin tunnels of subway, Fast Lagrangian Analysis of Continua (FLAC) software is used for this purpose. © 2014 Saudi Society for Geosciences.